Sumber Imajinasi Kreatif Ahmad Tohari dalam Menulis Karya Sastra (Source of Ahmad Tohari's Creative Imagination in Writing Literary Works) - Abdul Wachid Bambang Suharto; Endah Kusumaningrum (Indonesian Language Education and Literature, 2022)
The purpose of this writing is to describe Ahmad Tohari's creative imagination in composing literary works. Data was collected through interviews and document studies. The validity of the data is carried out through a Focus Group Discussion (FGD). The results of the study show Islamic ideology, and family as Ahmad Tohari's creative imagination in composing literary works. The beginning of Ahmad Tohari's writing journey was of course also heavily influenced by the family environment which had instilled the traits and character of a santri, even though Ahmad Tohari did not study at a pesantren. It was this background that made him close to the Nahdlatul Ulama and the big kiai with strong friendships. Ahmad Tohari also tries to continue to search for the meaning of life which is represented in the characters in the short stories. Islam is used as a source of life guidelines for ethics and aesthetics in the texts written by Ahmad Tohari.Tujuan penulisan ini untuk mendeskripsikan imajinasi kreatif Ahmad Tohari dalam menyusun karya sastra. Data dikumpulkan melalui wawancara dan studi dokumen. Keabsahan data dilakukan melaluiFocus Group Discussion (FGD). Hasil penelitian menunjukkan bahwa ideologi Islam, keluarga sebagai imajinasi kreatif Ahmad Tohari dalam menyusun karya sastra. Kebermulaan dari perjalanan menulis Ahmad Tohari tentunya juga banyak dipengaruhi oleh lingkungan keluarga yang telah menanamkan sifat dan karakter seperti halnya seorang santri, walaupun Ahmad Tohari tidak belajar di pesantren. Latar belakang itulah yang membuat ia dekat dengan kalangan Nahdlatul Ulama dan kiai besar dengan hubungan silaturahmi yang kuat. Ahmad Tohari juga berupaya terus melakukan pencarian makna hidup yang diwakilkan ke dalam tokoh-tokoh di dalam cerpen. Agama Islam dijadikan sebagai sumber pedoman hidup bagi etika dan estetika di dalam teks-teks yang ditulis oleh Ahmad Tohari.